Comprehensive Analysis of the Aberrance and Functional Significance of Ferroptosis in Gastric Cancer - Xiao, Jun; Zheng, Lingyan; Liu, Jingfeng (Frontiers in Pharmacology, 2022)
Objective: Ferroptosis is a type of iron-dependent necrosis related to cancer. Nevertheless, the features of ferroptosis in gastric cancer (GC) remain poorly understood. This study conducted a systematic analysis of ferroptosis regulators in GC. Methods: We gathered five GC cohorts including TCGA-STAD, GSE84437, GSE62254, GSE26901 and GSE15459. Unsupervised clustering analysis was adopted to cluster GC patients into different ferroptosis subtypes based on ferroptosis regulators. Immune cell infiltration and hallmark pathway activity were estimated via ssGSEA. Ferroptosis index was developed with PCA computational method. Response to chemotherapy agents and small molecular compounds was inferred via GDSC, CTRP and PRISM projects. Two anti-PD-1 therapy cohorts were gathered and the potential of FPI in predicting immune response was assessed. Results: Expression profiles, genetic mutations, DNA methylation, prognostic implications, and drug sensitivity of ferroptosis regulators were characterized in GC. Three ferroptosis subtypes were clustered with distinct prognosis, hallmark pathway activity and tumor-infiltrating immune cells. Ferroptosis levels were quantified based on the expression of prognostic ferroptosis-related signatures. The significant relationships between FPI and clinicopathological characteristics were observed. Furthermore, high FPI was in relation to poor prognosis, inflamed tumor microenvironment (TME) as well as high sensitivity to chemotherapy agents (docetaxel and cisplatin) and CTRP- and PRISM-derived compounds. Also, FPI acted as a promising predictor of immune response. Conclusion: Collectively, our findings identified a novel ferroptosis-based subtype classification of GC, and revealed the potential of ferroptosis in forming TME diversity and complexity and guiding individualized treatment.